2016
DOI: 10.7314/apjcp.2016.17.2.603
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of KRAS and BRAF Genes in Metastatic Colorectal Cancer: a First Large Scale Study from Iran

Abstract: Background: The investigation of mutation patterns in oncogenes potentially can make available a reliable mechanism for management and treatment decisions for patients with colorectal cancer (CRC). This study concerns the rate of KRAS and BRAF genes mutations in Iranian metastatic colorectal cancer (mCRC) patients, as well as associations of genotypes with clinicopathological features. Materials and Methods: A total of 1,000 mCRC specimens collected from 2008 to 2012 that referred to the Mehr Hospital and Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
15
1
2
Order By: Relevance
“…BRAF belongs to the family of RAF proteins and is an intracellular effector of the mitogen-activated protein kinase-signaling cascade ( 55 ). The BRAF V600E mutation is a molecular marker that has been reported in thyroid carcinoma ( 56 64 ). BRAF mutation rate was previously reported to be 29–83% in PTC, 37.5–77% in PTMC and 0.2–5.7% in benign thyroid disease ( 19 , 33 – 35 , 65 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF belongs to the family of RAF proteins and is an intracellular effector of the mitogen-activated protein kinase-signaling cascade ( 55 ). The BRAF V600E mutation is a molecular marker that has been reported in thyroid carcinoma ( 56 64 ). BRAF mutation rate was previously reported to be 29–83% in PTC, 37.5–77% in PTMC and 0.2–5.7% in benign thyroid disease ( 19 , 33 – 35 , 65 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…A thin 20-μm tissue section was obtained from the blocks, and deparaffinization was performed with xylene. Then, series of distilled water and graded ethanol solutions were used for rehydration, according to previous works [2] , [24] , [25] . The DNA purification was performed by using QIAamp DNA FFPE Tissue Kit (QIAGEN, Hilden, Germany), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…KRAS mutation was observed in 33.6% of CRC cases, which involves mutations at codon 12 and 13. There was a significant correlation between KRAS mutations and older ages and tumor type (non-mucinous) [68]. Incidence of mutation in codons 12 and 13 of KRAS was screened by another group among Iranian CRC subjects, showed that the codon 13 mutations had lower frequencies compared with codon 12 (8% vs. 24%).…”
Section: Main Textmentioning
confidence: 99%